PENGARUH SUMBER DAYA MANUSIA TERHADAP KUALITAS PELAYANAN (Studi Tentang Pengaruh Sumber Daya Manusia Terhadap Kualitas Pelayanan Di Kantor Pemerintah Kecamatan Kutorejo Kabupaten Mojokerto) - Herawati, Puri (JPAP: Jurnal Penelitian Administrasi Publik, 2018)
The best human resources in the organization give so important effect. The best of an organization is affected by the quality of the people. The government is an organization that is cooperation in their jobs description. In addition to quality, achieving goals, even operationally able to provide satisfactory service to the public. The problem of this studi is about significant influence between of human resources to service quality. This study aims to determine the significant influence of human resources to service quality. The method used quantitative data collection techniques used questionnaires with Likert scale or interval. Mechanical analysis used simple linear regression analysis by SPSS. There are 100 respondents surveyed in this study by answering statements based on questionnaires given to assess public opinion on the human resources and the effect to quality of service. Independent variables is human resource and the dependent variable is quality of service. The P-value of t test is 0,000 the value is less than 0,05 and the value of correlation is 0,821 or 82,1% (R2) and the coefficient determination is 0,674 or 67,4% (R). The result show that human resources affect significantly and correlation effectly to quality of service at Government Office of Kutorejo in Mojokerto. Â  Keywords: Human Resource, Quality of Service